Effect of hypoxia on production of caprine chimeric blastocyst - SURESH DINKAR KHARCHE; JUHI PATHAK; ANUJ KUMAR SINGH SIKARWAR; SONIA SARASWAT; RAVI RANJAN; SHIVAPRATAP SINGH (Indian Journal of Animal Sciences, 2022)
This study was conducted to evaluate the effect of 5% and 21% oxygen concentrations on chimeric embryo development. Inner cell mass (ICM) from parthenogenetic activated blastocyst were used to produce ES cell-like cells. A pair of zona-free tetraploid embryos and one clump of pESCs at passage 2 and 3 were aggregated on granulosa monolayer in such a manner that the clump of pESCs was sandwiched between the tetraploid embryos. The aggregates prepared were randomly divided into two groups viz. Group 1 (21% O2) (n=54) and Group 2 (5% O2) (n=50) followed by culture in humidified atmosphere of 5% CO2 at 38.5°C in a CO2 incubator. Aggregation rate and embryo quality was similar in both the groups. The percentage of aggregation, 8-16 cell, morula and blastocyst Group 1 (21% O2) was 91.66±4.04%, 49.07±5.08%, 25.92±6.05% and 16.66±4.95%, respectively while the percentage of aggregation, 8-16 cell, morula and blastocyst Group 2 (5% O2) was 96.59±2.83%, 51.89±9.14%, 16.28±5.52% and 28.40±8.10%, respectively. The aggregates and 8-16 cell stage embryos formed in Group 2 (5% O2) were comparatively higher than in Group 1 (21% O2) while morula formation in Group 2 (5% O2) was comparatively lower than in Group 1 (21% O2). Also, Group 2 (5% O2) had significantly more blastocysts as compared to Group 1 (21% O2). To conclude, culture under 5% O2 leads to improved aggregation and also enhances the production of blastocysts rather than with atmospheric oxygen concentrations (21%) during embryo incubation.